Sustainable Development in Cotton Sector through Industrial Applications of Value Added Products from Cotton Stalk - ARUDE, V. G.; SHUKLA, S. K.; PATIL, P. G.; DESHMUKH, P. S. (Cotton Research Journal, 2021)
Annually thirty million tonnes of cotton stalk is generated in India; most of which is treated as waste and burnt in fields leading to severe environmental pollution. ICAR-CIRCOT realised economic potential of value addition to cotton stalk and developed commercially viable and eco-friendly technologies for sustainable development in cotton sector. Cotton stalk supply chain model developed resulted in additional remuneration of Rs. 1500-2000/- per acre. Techno-economic feasibility of briquettes and pellets as renewable energy source resulted in establishment of around 50 briquetting and pelleting plants in Maharashtra as return on investment in briquetting and pelleting plant is 40% and 25% respectively. Utilization of pellets for cooking saves over 50% costs on LPG. ICAR - CIRCOT biomass based green crematorium found to be ecofriendly as it is good alternative to traditional wood based cremations and reduces deforestation and saves cost by 55%. Bio-enriched compost from cotton stalk has higher NPK which improves soil health and saves Rs. 9000/- per ha by replacing FYM. Oyster mushroom cultivation on cotton stalk showed that farmers can earn up to Rs. 6000/- per acre and that will help further improve nutritional security. These technologies helped to convert waste to wealth, and protect environment. Entrepreneurship and employment opportunities are created for rural youths for supply of cotton stalk as a raw material for industrial applications, establishment of briquetting and pelleting industry, compost making, manufacturing of crematorium and cultivation of mushroom. These business models would contribute to increased income opportunities for farmers and entrepreneurs, especially in rural areas, and more overall in cotton sector. These business models based on commercially viable technologies need to be promoted for sustainable development in cotton sector.